Photoabsorption of attosecond XUV light pulses by two strongly laser-coupled autoionizing states - Chu, Wei-Chun; Lin, C. D. (My University, 2012)
We study theoretically the photoabsorption spectra of an attosecond extreme ultraviolet (XUV) pulse by a laser-dressed atomic system. A weak XUV excites an autoionizing state which is strongly coupled to another autoionizing state by a laser. The theory was applied to explain two recent experiments [Loh, Greene, and Leone, Chem. Phys. 350, 7 (2008); Wang, Chini, Chen, Zhang, Cheng, He, Cheng, Wu, Thumm, and Chang, Phys. Rev. Lett. 105, 143002 (2010)] where the absorption spectra of the XUV lights were measured against the time delay between the laser and the XUV. In another example, we study an attosecond pulse exciting the 2s2p(1P) resonance of helium which is resonantly coupled to the 2s2(1S) resonance by a moderately intense 540-nm laser. The relation between the photoabsorption spectra and the photoelectron spectra and the modification of the transmitted lights in such an experiment are analyzed. The role of Rabi flopping between the two autoionizing states within their lifetimes is investigated with respect to the laser intensity and detuning.